Neuroinflammation Induced by Transgenic Expression of Lipocalin-2 in Astrocytes - Kim, Jae-Hong; Kwon, Osung; Bhusal, Anup; Lee, Jiyoun; Hwang, Eun Mi; Ryu, Hoon; Park, Jae-Yong; Suk, Kyoungho (Frontiers in Cellular Neuroscience, 2022)
Transgenic mice are a useful tool for exploring various aspects of gene function. A key element of this approach is the targeted overexpression of specific genes in cells or tissues. Herein, we report for the first time, the generation and characterization of conditional transgenic (cTg) mice for lipocalin-2 (LCN2) expression. We generated the R26-LCN2-transgenic (LCN2-cTg) mice that carried a loxP-flanked STOP (neo) cassette, Lcn2 cDNA, and a GFP sequence. When bred with Tg mice expressing Cre recombinase under the control of various tissues or cell-specific promoters, Cre-mediated recombination deletes the STOP cassette and allows the expression of LCN2 and GFP. In this study, we achieved the recombination of loxP-flanked LCN2 in hippocampal astrocytes of cTg mouse brain, using a targeted delivery of adeno-associated virus (AAVs) bearing Cre recombinase under the control of a GFAP promoter (AAVs-GFAP-mCherry-Cre). These mice with localized LCN2 overexpression in astrocytes of the hippocampus developed neuroinflammation with enhanced glial activation and increased mRNA and protein levels of proinflammatory cytokines. Furthermore, mice showed impairment in cognitive functions as a typical symptom of hippocampal inflammation. Taken together, our study demonstrates the usefulness of LCN2-cTg mice in targeting specific cells at various organs for conditional LCN2 expression and for subsequent investigation of the functional role of cell-type-specific LCN2 within these sites. Moreover, the LCN2-cTg mice with targeted expression of LCN2 in hippocampal astrocytes are a new in vivo model of neuroinflammation.